Analisis Strategi Regulasi Emosi Cognitive Reappraisal untuk Menurunkan Perilaku Cyberbullying - Ratna Wulandari; Nur Hidayah (Indonesian Journal of Educational Counseling, 2018)
ANALYSIS OF COGNITIVE REAPPRAISAL EMOTIONAL REGULATORY STRATEGIES TO REDUCE CYBERBULLYING BEHAVIOR. Cyberbullying is a behavior of intimidating, mocking, humiliating or disturbing others, either individually or in groups conducted in cyberspace such as social media such as facebook, instagram, twitter, BBM, and whatsapp. To be able to reduce the tendency of cyberbullying behavior can be done by way of emotional regulation using cognitive reappraisal strategy, because it is known that the emotional condition can affect individual behavior. Emotional regulation is a process in which individuals influence, control, and adapt their emotions, when they have them, and how they feel and express these emotions at the right level of intensity to achieve a goal. Emotion regulation strategy that can be used one of them is cognitive reappraisal emotional regulation strategy. The purpose of this theory is to examine the application of cognitive reappraisal emotional regulation strategy to decrease the tendency of cyberbullying behavior of students.